The Description of Solomon's Wedding: Song 3:6-11 as a Key to the Overall Understanding of the Song of Songs - Schellenberg-Lagler, Annette (Vetus Testamentum, 2020)
This article argues that Song of Songs 3:7-11 is a mocking song about King Solomon and was not originally connected with 3:6. After presenting aspects of 3:7-11 that might convey criticism of Solomon, the thesis is further substantiated by observations showing that taking Solomon as a cipher for the nonroyal human lover or a divine lover does not work in this passage. The article concludes by pointing out some consequences of this analysis for the overall understanding of the Song.